Analysis of binding interfaces of the human scaffold protein AXIN1 by peptide microarrays - Harnoš, Jakub; Ryneš, Jan; Víšková, Pavlína; Foldynová-Trantírková, Silvie; Bajard-Ešner, Lola; Trantírek, Lukáš; Bryja, Vítězslav (The Journal of biological chemistry, 2018)
Intrinsically disordered regions (IDRs) are protein regions that lack persistent secondary or tertiary structure under native conditions. IDRs represent >40% of the eukaryotic proteome and play a crucial role in protein-protein interactions. The classical approach for identification of these interaction interfaces is based on mutagenesis combined with biochemical techniques such as coimmunoprecipitation or yeast two-hybrid screening. This approach either provides information of low resolution (large deletions) or very laboriously tries to precisely define the binding epitope via single amino acid substitutions. Here, we report the use of a peptide microarray based on the human scaffold protein AXIN1 for high-throughput and -resolution mapping of binding sites for several AXIN1 interaction partners in vitro For each of the AXIN1-binding partners tested, i.e. casein kinase 1 ϵ (CK1ϵ); c-Myc; peptidyl-prolyl cis/trans isomerase, NIMA-interacting 1 (Pin1); and p53, we found at least three different epitopes, predominantly in the central IDR of AXIN1. We functionally validated the specific AXIN1-CK1ϵ interaction identified here with epitope-mimicking peptides and with AXIN1 variants having deletions of short binding epitopes. On the basis of these results, we propose a model in which AXIN1 competes with dishevelled (DVL) for CK1ϵ and regulates CK1ϵ-induced phosphorylation of DVL and activation of Wnt/β-catenin signaling.
Keywords: Casein Kinase 1 epsilon; signální dráha Wnt; Dishevelled Proteins; scaffold protein; Protein Binding; Myc (c-Myc); dishevelled; Phosphorylation; casein kinase 1ϵ; Axin Protein; axin; serine/threonine protein kinase; kaseinkinasa Iepsilon; beta Catenin; peptide array; p53; Peptides; protein dishevelled; kompetitivní vazba; čipová analýza proteinů; Protein Array Analysis; axin protein; Humans; Protein Interaction Domains and Motifs; Binding Sites; Binding, Competitive; vazba proteinů; interakční proteinové domény a motivy; Wnt pathway; peptidy; Wnt Signaling Pathway; fosforylace; Wnt Proteins; beta-katenin; intrinsically disordered region; vazebná místa; lidé; proteiny Wnt